Antibacterial, antibiofilm, and antiquorum sensing activities of phytosynthesized silver nanoparticles fabricated fromMespilus germanicaextract against multidrug resistance ofKlebsiella pneumoniaeclinical strains. (29th January 2020) - Foroohimanjili, Fatemeh; Mirzaie, Amir; Hamdi, Seyed Mohammad Mehdi; Noorbazargan, Hassan; Hedayati Ch, Mojtaba; Dolatabadi, Aghigh; Rezaie, Hossein; Bishak, Faezeh M.
Abstract: The aim of the present work was to investigate the antibacterial, antibiofilm, and antiquorum sensing activities of phytosynthesized silver nanoparticles (AgNPs) fabricated from Mespilus germanica extract against multidrug‐resistant (MDR) Klebsiella pneumoniae strains. Fifty strains of K. pneumoniae were isolated from various clinical specimens. Biofilm‐forming strains were identified using Congo red agar and polymerase chain reaction (PCR) techniques. Subsequently, the antibacterial activity of phytosynthesized AgNPs on MDR K. pneumoniae strains was investigated by broth microdilution assay and agar well‐diffusion method. Finally (in the last step), the antibiofilm activity of phytosynthesized AgNPs was determined using microtiter plate assay and real‐time PCR (RT‐PCR) methods for the analysis of type 3 fimbriae ( mrkA ) and quorum‐sensing system ( luxS ) gene expression. The results of this study showed that the phytosynthesized AgNPs had a spherical nanostructure with the mean size of 17.60 nm. The AgNPs exhibited dose‐dependent antibacterial activity. The results of the microtiter plate and RT‐PCR methods show that AgNPs inhibited the biofilm formation in MDR K. pneumoniae strains, and the expressions of mrkA and luxS genes were downregulated significantly in MDR strains after treatment with a subminimum inhibitory concentration of AgNPs. In conclusion, AgNPs effectively prevent the formation of biofilms and kill bacteria in established biofilms, which suggests that AgNPs might be a promising candidate for the prevention and treatment of biofilm‐related infections caused by MDR K. pneumoniae strains.